2020
DOI: 10.1155/2020/9723563
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Week Gait Retraining Reduced Patellofemoral Joint Stress during Running in Male Recreational Runners

Abstract: Purpose. To explore the changes in knee sagittal angle and moment and patellofemoral joint (PFJ) force and stress before and after 12-week gait retraining. Methods. A total of 30 healthy male recreational runners were randomized into a control group (n=15) who ran in their original strike pattern using minimalist shoes or experimental group (n=15) who ran in a forefoot strike pattern using minimalist shoes during the 12-week gait retraining. The kinematic and kinetic data of the dominant leg of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For the GR group, the participants were asked to wear minimalist shoes and ran outdoor with the FFS at a moderate self-selected speed during training. The FFS referred to the initial metatarsal ball of the forefoot contact followed by the contact of the rest of the foot [ 15 ]; in this running style, the feet were placed below the hip during ground contact [ 18 ]. The training intervention lasted for 12 weeks, and the training sessions were executed three times per week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the GR group, the participants were asked to wear minimalist shoes and ran outdoor with the FFS at a moderate self-selected speed during training. The FFS referred to the initial metatarsal ball of the forefoot contact followed by the contact of the rest of the foot [ 15 ]; in this running style, the feet were placed below the hip during ground contact [ 18 ]. The training intervention lasted for 12 weeks, and the training sessions were executed three times per week.…”
Section: Methodsmentioning
confidence: 99%
“…During the GR intervention, foot and ankle exercises (i.e., heel raises, short foot exercise, and towel curl exercise) were encouraged to be conducted before each GR session as a warm-up exercise to prevent injuries for participants in the GR group. The detailed training plan and supervision methods can be found in our previous studies [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
“…We identified 27 studies that reported PFJRF during running 25 26 34 35 38 39 50 52 56–59 61 68 69 74–76 78 80–82 87 90 91 93 94. Pooled peak PFJRF in healthy individuals was 5.2±1.2 BW25 35 38 39 52 56–58 61 68 74 80–82 87 90 94 based on 17 studies and 4.1±0.9 BW in individuals with patellofemoral pain34 38 78 based on three studies during running (figure 3). The average running speed ranged from 2.33 m/s to 4.47 m/s in healthy individuals and 2.77 m/s to 4.00 m/s in individuals with patellofemoral pain.…”
Section: Resultsmentioning
confidence: 99%
“…For the subsequent 11 weeks, the INT group underwent centralized training on an indoor track on our campus once a week. The foot core exercise protocol was based on previous literature and previous results of our team, and it had shown to be effective in enhancing foot muscles and potentially reducing the risk of injury ( Warne et al, 2014 ; Ridge et al, 2019 ; Wang B et al, 2020 ; Zhang et al, 2021 ). It included heel raises, towel curls, foot doming, toe spread, balance board, and foot relaxation exercises by stepping on a tennis ball with progressive intensity ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%